Diode-end-pumped Nd:YVO4 slab laser with a compact negative confocal hybrid resonator. (8th June 2015) - Mao, Y F; Zhang, H L; Cui, L; Xu, L; Xing, J C; Xin, J G
Abstract: Laser diode-end-pumped Nd:YVO4 slab laser with a hybrid resonator operating at 1064 nm was carried out. The size of Nd:YVO4 crystal with 0.3 at.% doped concentration was 14 mm × 10 mm × 1 mm, which was cut along the a axis and the c axis was parallel with the 14 mm direction. By using a compact negative confocal unstable-stable hybrid resonator, 134 W 1064 nm laser output was realized with the M 2 factors in the unstable direction and in the stable direction were 2.1 and 1.7 respectively. The slope efficiency and optical-to-optical efficiency were 49.3% and 40.2%, respectively.